GAIRAIGO: Kata Serapan Bahas Asing dalam Perkembangan Bahasa Jepang - Suartini, Ni Nengah (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2010)
Gairaigo is loanwords in Japanese. Gairaigo refers to words that come from foreignlanguages, except China. This gairaigo is written in Japanese phonetic script which iscalled Katakana. Since 16c Japan has interaction with foreign countries, mainly withPortuguese. Through this interaction Japanese borrowed words from foreign languages.After the reopening of Japan in 19c, the absorption of foreign words especiallyfrom European and English predominate. Loanwords are used for concepts which donot exist in Japanese, euphemism and also for other reasons such as status marking orfashionability. When a foreign word containing a consonant cluster is borrowed intoJapanese, it is modified substantially because in Japanese every consonant must befollowed by a vowel. In Japanese language, loanwords are unique and various. Abbreviationsuch as ‘terebi (from terebishion, television)’, portmanteous such as ‘dijikame(dijitaru kamera, digital camera)’, loanblends, Japanese words that combine withother foreign words such as ‘haburashi’ is a blend of Japanese ‘ha (teeth)’ and English‘burashi (brush)’, chanpon’go, combination of two different foreign languages such as‘puchi hoteru’ small hotel derives from ‘petit (french)’ and ‘hoteru (hotel)’, waseieigo,‘made in Japan’ English such as ‘sarariiman’ (salary man) refers to salaried worker. Dueto Japanese pronunciation rules and its mora-based phonology, the pronunciationhas changed to the original language, the variuos forms and the use of gairaigo whichdo not reflect its original meaning make the foreigners who learn Japanese as foreignlanguage find is hard to recognize gairaigo.Key words : gairaigo, foreign language, loanword